2013
DOI: 10.1074/jbc.m113.489708
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hypoxia-inducible Factor 1α (HIF-1α) by Lysophosphatidic Acid Is Dependent on Interplay between p53 and Krüppel-like Factor 5

Abstract: Background: LPA induces HIF-1␣ expression, but the underlying mechanism remains unknown. Results: LPA induced HIF-1␣ by decreasing p53 expression, and additionally, KLF5 transactivated HIF-1␣ expression. Conclusion: KLF5 and p53 reciprocally regulate HIF-1␣ expression. Significance: This study provides a new dimension to understanding how LPA promotes colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 55 publications
2
57
0
Order By: Relevance
“…20 Unsaturated LPAs are produced during mild oxidation of LDL and induce the upregulation of Hif1a expression by activating LPA receptors in cancer cells and in smooth muscle cells. 21,22 In line with these reports, our findings indicate that hyperlipidemia-induced endothelial HIF-1α activation is because of LPA receptor signaling triggered by moxLDL-derived LPAs. 6 In addition, LPAs activate proatherogenic NF-κB signaling in ECs.…”
Section: Discussionsupporting
confidence: 80%
“…20 Unsaturated LPAs are produced during mild oxidation of LDL and induce the upregulation of Hif1a expression by activating LPA receptors in cancer cells and in smooth muscle cells. 21,22 In line with these reports, our findings indicate that hyperlipidemia-induced endothelial HIF-1α activation is because of LPA receptor signaling triggered by moxLDL-derived LPAs. 6 In addition, LPAs activate proatherogenic NF-κB signaling in ECs.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, the adrenoreceptors have been shown to functionally interact with opioid receptors (43), which elicit protective actions in response to pre-and post-conditioning stimuli upon cardiac and cerebral damages (44,45). It is worth noting that certain ligand-activated GPCRs induce HIF-1 expression and function (46)(47)(48), thus mimicking hypoxic conditions. For instance, the recruitment of transcription factors to the promoter sequence of HIF-1 as well as the stabilization of HIF-1 protein levels may occur upon activation of GPCRs by endothelin-1 (ET-1), β-adrenoceptor agonists, and lysophosphatidic acid (46)(47)(48).…”
Section: Gpcr Involvement In Hypoxia-mediated Signalingmentioning
confidence: 99%
“…It is worth noting that certain ligand-activated GPCRs induce HIF-1 expression and function (46)(47)(48), thus mimicking hypoxic conditions. For instance, the recruitment of transcription factors to the promoter sequence of HIF-1 as well as the stabilization of HIF-1 protein levels may occur upon activation of GPCRs by endothelin-1 (ET-1), β-adrenoceptor agonists, and lysophosphatidic acid (46)(47)(48).…”
Section: Gpcr Involvement In Hypoxia-mediated Signalingmentioning
confidence: 99%
“…In a recent research about colon cancer, the authors suggested that LPA induced proliferation of colon cancer cells through upregulation of HIF1α by dynamically modulating its interaction with KLF5 and P53. 70 Another research about colon cancer found that LPA stimulated proliferation of colon cancer cells by activation of β-catenin through multiple pathways involving phosphorylation of GSK-3 and β-catenin, and enhancing β-catenin interaction with TCF4, which could be enhanced by KLF5 via increasing the β-catenin-TCF4 interaction. 71 ATX has been reported to act as a motility and growth factor in a variety of cancer cells, and has important functions in cell migration and proliferation.…”
Section: Expression Of Atx/lpa Axis In Cancermentioning
confidence: 99%